Psychological exhaustion of nursing professionals who care for patients with neoplasms - Guilherme Gasparini Camargo; Maria Giovana Borges Saidel; Maria Inês Monteiro (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Identify, analyze and understand the social representations of nursing professionals about burnout syndrome. Method: Qualitative study with nursing professionals who worked in the direct assistance to oncologic patients, conducted through semi-structured interview, using the technique of content analysis, anchoring the interpretations in the theory of social representations. Results: Seven professionals participated; after analysis, two categories emerged: "The stress of professionals, the naturalization of suffering and self-care strategies"; and "Ressignifications, learning in the oncologic sector and network gaps". The representations about stress and the relationship of the professionals with the daily practice were predominant. Final Considerations: The nursing professionals represented the burnout syndrome socially as stress and made important reflections on the subject in the context of daily work. Concepts that determine the behavior of professionals were perceived as mechanisms of confrontation. In the vision of this social group, spirituality was revealed as a therapeutic strategy.